Indicating Dependency between Spoken Sentences by Prosodic Means - Mari Wiklund (Discours)
In certain languages and in certain types of data, prosodic features are used to group prosodic units called by some scholars spoken sentences into larger units, often called speech paragraphs. The onsets of the first spoken sentences of these units are marked by a raised pitch level compared to the beginning of the preceding spoken sentence. The prosodic units that are formed typically correspond to topical entities. Prosodic means are also used to indicate relationships between spoken sentences belonging to the same speech paragraph. A new spoken sentence generally starts at a higher pitch compared to the end of the preceding spoken sentence. However, if two consecutive spoken sentences are closely related, the second begins at a lower pitch vis-à-vis the end of the previous spoken sentence, but the subsequent syllable of the new spoken sentence displays raised pitch. This phenomenon of sentence-initial lowered pitch indicates, on one hand, a close discourse relationship with the preceding spoken sentence but, on the other, the beginning of a grammatically independent spoken sentence. The data are in Finnish, and they come from conference-like, monologous presentations that are translated by speech-to-text interpreters to allow the speech to be accessed by the deaf and hard-of-hearing. The analyses are performed using instrumental phonetics methodology.